Projection of Manpower Requirements for the Sarawak Economy - Mohd Khairul Hisyam, Bin Hassan; Muhammad Asraf, Bin Abdullah; Audrey, Liwan (Human Resource Management Academic Research Society (HRMARS), 2019)
Through the use of the manpower requirement approach (MRA), this paper attempts to forecast the manpower requirements for the Sarawak economy in 2025. The MRA is used as the method for estimating the manpower as it is contended that the manpower requirement forecast is strongly related to the labour demand. Hence, it can be concluded that the manpower inventory and analysis provide valuable information pertaining to the present and future workers needed at each level. Although the information may not be completely accurate, it is still valuable and useful for providing a basis for the recruitment, selection, and training process. The projection for the manpower requirements in the manufacturing sector clearly shows a high demand. The results reveal that agriculture is the main sector that contributes to the job opportunities in the Sarawak economy while the skilled agriculture, forestry, and fishery workers are the main employment categories for the Sarawak economy in 2025.